PENGARUH HEDONIC SHOPPING VALUE DAN STORE ATMOSPHERE TERHADAP IMPULSIVE BUYING PADA KONSUMEN CARREFOUR DI PONTIANAK - Diana Fitriani (Universitas Raharja, 2018)
The main purpose of this research is to assess the effect of hedonic shopping value and store atmosphere to the impulsive buying of Carrefour consumen in Pontianak. Double analysis resgresion is the research method used with SPSS version 20.0. Ordinary least square analysis as valid assessment of research. Study research with descriptive analysis method applied. Hedonic shopping value (X1), store atmosphere (X2) is the independent variable, the dependent variabel that is impulsive buying (Y). Questioner as the instrument and research variabel consists of questioner using assessment method based on Silvera theory for independent variabel, otherwise the dependent variabel based on Rachmawati teory and likert scale as the assessment used. The population based on Disdukcapil data is 653.611,the number of respondents accepted is 100 people and accidental sampling as the sampling technique. Based on the partial research, then it is gained 31,92% for store atmosphere variabel (X2) to impulsive buying, otherwise hedonic shopping value (X1) is1,90%. The simultaneous research gained is 59,2% for hedonic shopping value variabel (X1) and store atmosphere (X2) effect positively. The result shows that store atmosphere at Carrefour Pontianak effect consumers in shopping his effect consumers in shopping his money more than hedonic shopping value